Optoelectronic synapse device and method of manufacturing the same
Patent Information
- Application Number
- CN202611062180.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]有鉴于此,本发明提出了一种光电突触器件及其制备方法,以解决现有的光电突触器件存在的难以充分生成光生载流子并实现对有效载流子进行高效捕获的技术问题
[0016]本发明的光电突触器件相对于现有技术具有以下有益效果:通过设置包括层叠的Cs2AgBiBr6钙钛矿层及CuAlS2量子点层的复合光吸收层,当使用450nm蓝光作为入射光时,光子能量有效且充分地被Cs2AgBiBr6钙钛矿材料吸收并产生光生载流子,光生电子被CuAlS2量子点材料的缺陷态高效捕获形成载流子俘获中心,从而有效抑制了有效载流子的传输与分离,降低了光电突触器件的整体导电性,使光电突触器件表现抑制性反向光电导行为,实现了光电突触器件的突触权重的即时光擦除功能。
Smart Images

Figure CN122892276A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photoelectric synapse device technology, and in particular to a photoelectric synapse device and its preparation method. Background Technology
[0002] As the scale of artificial intelligence continues to expand, the amount of data computation required for model training is increasing daily. However, traditional computing devices face serious energy consumption and latency problems when processing massive amounts of information due to the need for data transmission between memory and arithmetic units. Inspired by the working mode of the brain, neuromorphic computing utilizes memristor devices to record the history of signal stimulation by the electrical conductance state, simulating the functions of biological neurons and synapses to achieve in-memory computing integration. This type of device has become an ideal solution to overcome the limitations of traditional in-memory computing architectures and complete large-scale data processing with low energy consumption. As the core component for achieving memristor characteristics in neuromorphic computing, synaptic devices need to have the ability to change their own conductivity after receiving signal stimulation, thereby achieving in-memory (resistance change) and computing (stimulus accumulation) integration. Purely electrical synapses rely on external voltage pulses to adjust weights for memristor effects, which has fundamental physical limitations such as resistance-capacitance delay and heat generation, causing additional latency and energy consumption problems. Optoelectronic synaptic devices use optical signals to regulate the carrier concentration and conductive pathways of the device to achieve conductivity adjustment, thereby achieving signal weight adjustment. With their extremely fast optical signal transmission speed and extremely low heat loss, optoelectronic synaptic devices have become an ideal candidate to replace pure electrical synapses in realizing neuromorphic computing, providing a brand-new solution for ensuring computing power in artificial intelligence.
[0003] In biological vision systems, excitatory signals alone are insufficient for more complex perceptual functions; synergistic regulation of excitatory and inhibitory signals is necessary to maintain a dynamic balance in synaptic signal transmission. For photoelectric synaptic devices, effective signal processing requires simultaneous "memory" and "erasure" effects, and consequently, "write" and "reset" signals. Existing photoelectric synaptic devices often employ voltage modulation to achieve bidirectional modulation of memristor characteristics. This method alters the carrier transport path by adjusting the device bias voltage, thereby switching memristor modes. However, this approach suffers from resistance-capacitance delay during read-in and erase-out mode switching, leading to reduced computational speed. Furthermore, adjusting the bias voltage may cause ion migration issues within the device, decreasing its stability. Fully optically controlled photoelectric synaptic devices utilize incident light of different wavelengths to excite differentiated carrier transport behaviors, achieving a fully optically controlled dual-mode memristor effect for both memory and erase. For example, photoelectric synapses based on Bi₂O₂Se / graphene sensitive layers achieve fully optically controlled dual-mode response by matching the band structures of the two materials and controlling the transport behavior of charge carriers near the Dirac point under 635 and 365 nm light irradiation. However, due to the thickness of the two-dimensional material, the light absorption effect of this type of photoelectric synapse is poor, and the processing equipment required for two-dimensional materials, such as vapor deposition, is complex and costly. Photoelectric synapses based on InGaZnO homojunctions achieve continuous enhancement and reduction of conductivity by controlling the oxygen vacancy concentration under 800 and 420 nm wavelength light irradiation. Fully optically controlled photoelectric synapses based on metal oxides such as ZnO and Ga₂O₃ have also been developed. However, metal oxide-type photoelectric synapses achieve memristor performance by slowly forming or releasing surface vacancies and conductive channels, requiring multiple stimulations to reset conductivity, resulting in energy consumption and delay issues.
[0004] Therefore, there is an urgent need for a photoelectric synapse device and its fabrication method to solve the above-mentioned technical problems. Summary of the Invention
[0005] In view of this, the present invention proposes a photoelectric synapse device and its fabrication method to solve the technical problem that existing photoelectric synapse devices are unable to fully generate photogenerated carriers and achieve efficient capture of effective carriers.
[0006] The technical solution of this invention is implemented as follows: In a first aspect, the present invention provides a photoelectric synapse device, comprising: grassroots level; An electron transport layer is located on one side of the base layer; A composite light absorption layer is located on the side of the electron transport layer away from the base layer, and the composite light absorption layer is in contact with the electron transport layer; A top electrode layer is located on the side of the composite light absorption layer away from the electron transport layer, and the top electrode layer is in contact with the composite light absorption layer; The composite light absorption layer comprises a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer stacked together. The Cs2AgBiBr6 perovskite layer is in contact with the electron transport layer, and the CuAlS2 quantum dot layer is located on the side of the Cs2AgBiBr6 perovskite layer away from the electron transport layer.
[0007] Based on the above technical solutions, preferably, the electron transport layer is selected from at least one of ZnO material and SnO2 material; The thickness of the electron transport layer is 30nm~150nm.
[0008] Based on the above technical solutions, preferably, the material of the Cs2AgBiBr6 perovskite layer is Cs2AgBiBr6 perovskite material, and the material of the CuAlS2 quantum dot layer is CuAlS2 quantum dot material. The thickness of the composite light-absorbing layer is 215nm~473nm, the thickness of the Cs2AgBiBr6 perovskite layer is 126nm~252nm, and the thickness of the CuAlS2 quantum dot layer is 89nm~221nm. The thickness ratio of the CuAlS2 quantum dot layer to the Cs2AgBiBr6 perovskite layer is (0.46~1.07):1.
[0009] Secondly, the present invention also provides a method for fabricating a photoelectric synaptic device, comprising: Provide for the grassroots; An electron transport layer is formed on one side of the base layer; A composite light absorption layer is formed on the side of the electron transport layer away from the base layer, and the composite light absorption layer is in contact with the electron transport layer; A top electrode layer is formed on the side of the composite light absorption layer away from the electron transport layer, and the top electrode layer is in contact with the composite light absorption layer; The composite light absorption layer comprises a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer stacked together. The Cs2AgBiBr6 perovskite layer is in contact with the electron transport layer, and the CuAlS2 quantum dot layer is located on the side of the Cs2AgBiBr6 perovskite layer away from the electron transport layer.
[0010] Based on the above technical solutions, preferably, the step of forming a composite light absorption layer on the side of the electron transport layer away from the substrate includes: Provide Cs2AgBiBr6 precursor solution and CuAlS2 quantum dot dispersion; The substrate, the electron transport layer, and the Cs2AgBiBr6 precursor solution are preheated. The Cs2AgBiBr6 precursor solution forms a Cs2AgBiBr6 precursor layer on the surface of the electron transport layer away from the substrate. The CuAlS2 quantum dot dispersion forms a CuAlS2 quantum dot dispersion layer on the surface of the Cs2AgBiBr6 precursor layer away from the electron transport layer. The composite light-absorbing layer is obtained by heat-treating the Cs2AgBiBr6 precursor layer and the CuAlS2 quantum dot dispersion layer. The temperature of the preheating treatment is 70℃~85℃, and the time of the preheating treatment is 5min~10min; The temperature of the heat treatment is 280℃~320℃, and the time of the heat treatment is 5min~10min.
[0011] Based on the above technical solution, preferably, the preparation steps of the Cs2AgBiBr6 precursor solution include: CsBr, BiBr3 and AgBr are mixed in a molar ratio of 2:(1.0~1.2):(1.0~1.2) in a first solvent and dispersed to obtain the Cs2AgBiBr6 precursor solution. Wherein, the first solvent is dimethyl sulfoxide, the dispersion treatment temperature is 55℃~75℃, and the dispersion treatment time is greater than or equal to 12 hours.
[0012] Based on the above technical solutions, preferably, the preparation steps of the CuAlS2 quantum dot dispersion include: CuCl and Al(acac)3 are mixed in a molar ratio of 1:(0.8~1.2) in a second solvent, and after degassing, a first mixture is obtained. The first mixture is kept at 100℃~160℃ for 30 minutes or more to obtain the first reaction solution; The first reaction solution is kept at 145℃~160℃ for 15 minutes or more to obtain the second reaction solution; The second reaction solution is mixed with n-dodecyl mercaptan to obtain the third reaction solution; The third reaction solution is mixed with the sulfur precursor solution at 160℃~170℃ for 4 minutes and then kept at this temperature for 5 minutes to obtain the fourth reaction solution. The fourth reaction solution is reacted sequentially with the zinc shell precursor solution and the selenium shell precursor solution at 160℃~170℃ to obtain the fifth reaction solution. The fifth reaction solution was kept at 220℃~240℃ for more than or equal to 50 min to obtain CuAlS2 quantum dot stock solution; The CuAlS2 quantum dot stock solution was purified to obtain the CuAlS2 quantum dot dispersion.
[0013] Based on the above technical solution, preferably, the second solvent is a mixed solvent of 1-octadecene and oleic acid, wherein the volume ratio of 1-octadecene to oleic acid in the second solvent is 1:(0.8~1.2). The sulfur precursor solution is obtained by dissolving thioacetamide in a third solvent, which is a mixed solvent of 1-octadecene and n-dodecyl mercaptan, with a volume ratio of 1-octadecene to n-dodecyl mercaptan of (6~12):(1.5~4), and the concentration of thioacetamide is 0.00469 g / mL~0.00939 g / mL. The zinc shell precursor solution was obtained by dissolving Zn(St)2 in 1-octadecene, and the concentration of the zinc shell precursor was 0.125 g / mL to 0.188 g / mL. The selenium shell precursor solution was obtained by dissolving Se powder in 1-octadecene, and the concentration of the selenium shell precursor was 0.0131 g / mL to 0.0196 g / mL.
[0014] Based on the above technical solutions, preferably, the step of purifying the CuAlS2 quantum dot stock solution to obtain the CuAlS2 quantum dot dispersion includes: The CuAlS2 quantum dot stock solution was mixed with the fourth solvent and then subjected to a first centrifugation process to obtain the supernatant. The supernatant was mixed with the fifth solvent and then subjected to a second centrifugation process to obtain CuAlS2 quantum dots. After drying, the CuAlS2 quantum dots are mixed with a sixth solvent to obtain the CuAlS2 quantum dot dispersion. Wherein, the fourth solvent is selected from toluene, the fifth solvent is selected from anhydrous ethanol, and the sixth solvent is selected from toluene; The first centrifugation process is carried out at a speed of 3000 rpm to 5000 rpm for a duration of 3 min to 5 min. The second centrifugation process is carried out at a speed of 12,000 rpm to 16,000 rpm for 5 to 10 minutes.
[0015] Based on the above technical solutions, preferably, the step of forming a top electrode layer on the side of the composite light absorption layer away from the electron transport layer includes: The top electrode layer is formed on the surface of the composite light absorption layer away from the electron transport layer using a photomask.
[0016] The photoelectric synaptic device of the present invention has the following advantages over the prior art: by setting a composite light absorption layer including a stacked Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer, when 450nm blue light is used as incident light, the photon energy is effectively and fully absorbed by the Cs2AgBiBr6 perovskite material to generate photogenerated carriers. The photogenerated electrons are efficiently captured by the defect states of the CuAlS2 quantum dot material to form carrier trapping centers, thereby effectively suppressing the transmission and separation of effective carriers, reducing the overall conductivity of the photoelectric synaptic device, and enabling the photoelectric synaptic device to exhibit suppressive reverse photoconductive behavior, thus realizing the instantaneous light erasure function of the synaptic weight of the photoelectric synaptic device. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 A scanning electron microscope (SEM) image of a photoelectric synaptic device provided in Embodiment 1 of the present invention; Figure 2 Transmission electron microscopy (TEM) results of CuAlS2 quantum dot material used in the CuAlS2 quantum dot layer of a photoelectric synaptic device provided in Embodiment 1 of the present invention; Figure 3 (a) A graph showing the PPF characteristics of a photoelectric synaptic device provided in Embodiment 1 of the present invention under two consecutive light pulses stimulated by 380nm light; Figure 3 (b) A diagram showing the synaptic plasticity of a photoelectric synaptic device provided in Embodiment 1 of the present invention under different light pulse widths under 380nm light stimulation; Figure 3 (c) A diagram showing the synaptic plasticity of a photoelectric synaptic device provided in Embodiment 1 of the present invention under different numbers of light pulses under 380nm light stimulation; Figure 4 The response time of a photosynaptic device under 450nm light stimulation is shown in Embodiment 1 of the present invention. Figure 5 The diagram shows the different response results of a photoelectric synaptic device under 380nm and 450nm light stimulation, as provided in Embodiment 1 of the present invention. Detailed Implementation
[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0020] Currently, existing opto-synaptic devices face the technical challenge of failing to adequately generate photogenerated carriers and efficiently capture effective carriers.
[0021] In a first aspect, the present invention provides a photoelectric synapse device, comprising: grassroots level; An electron transport layer is located on one side of the base layer; A composite light absorption layer is located on the side of the electron transport layer away from the base layer, and the composite light absorption layer is in contact with the electron transport layer; A top electrode layer is located on the side of the composite light absorption layer away from the electron transport layer, and the top electrode layer is in contact with the composite light absorption layer; The composite light absorption layer comprises a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer stacked together. The Cs2AgBiBr6 perovskite layer is in contact with the electron transport layer, and the CuAlS2 quantum dot layer is located on the side of the Cs2AgBiBr6 perovskite layer away from the electron transport layer.
[0022] The photoelectric synaptic device provided in this application, by setting a composite light absorption layer including a stacked Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer, when using 450nm blue light as incident light, the photon energy is effectively and fully absorbed by the Cs2AgBiBr6 perovskite material to generate photogenerated carriers. The photogenerated electrons are efficiently captured by the defect states of the CuAlS2 quantum dot material to form carrier trapping centers, thereby effectively suppressing the transmission and separation of effective carriers, reducing the overall conductivity of the photoelectric synaptic device, and enabling the photoelectric synaptic device to exhibit suppressive reverse photoconductive behavior, thus realizing the instantaneous light erasure function of the synaptic weight of the photoelectric synaptic device.
[0023] Specifically, the CuAlS2 quantum dot layer of this application uses CuAlS2 quantum dots to construct a carrier-efficient trapping structure by leveraging their dense defects and trap states. This allows for timely and efficient trapping of photogenerated carriers generated by the Cs2AgBiBr6 perovskite layer, achieving a photoinduced suppression effect. This facilitates the acquisition of fully optically controlled neuromorphic opto-synaptic devices that can be written to multiple times and reset with a single illumination, providing a convenient and efficient memristor device for neuromorphic computing.
[0024] In some embodiments, the substrate comprises indium tin oxide (ITO) material. The substrate may be a commercially available ITO glass substrate.
[0025] In some embodiments, the electron transport layer is selected from at least one of ZnO and SnO2 materials.
[0026] Taking ZnO material as an example, when ZnO material is used for the electron transport layer, under 380nm ultraviolet light, the incident photons mainly excite ZnO to generate photogenerated carriers. At the same time, oxygen vacancies in ZnO are ionized, providing additional carriers for the photoelectric synapse device, so that the photoelectric synapse device exhibits a positive photoconductive response. When the light is removed, the photogenerated carriers gradually recombine, but some electrons are trapped by defects such as oxygen vacancies for a long time, resulting in a slow decay trend of conductivity. Moreover, the steady-state current is significantly higher than the initial dark-state current, thereby realizing the excitatory synaptic enhancement and photowriting characteristics of the photoelectric synapse device.
[0027] Taking ZnO material as an example, the specific mechanism of writing / resetting of the photoelectric synapse device is as follows: Under 380 nm ultraviolet light, the incident photons mainly excite ZnO to generate photogenerated carriers, while oxygen vacancies in ZnO are ionized, providing additional carriers for the photoelectric synapse device, making the photoelectric synapse device exhibit a positive photoconductive response; when the light is removed, the photogenerated carriers gradually recombine, but some electrons are trapped by defects such as oxygen vacancies for a long time, resulting in a slow decay trend in conductivity, and the steady-state current is significantly higher than the initial dark-state current, thereby realizing the excitatory synaptic enhancement and photowriting characteristics of the photoelectric synapse device; when the incident light is 450 nm... When emitting nm blue light, the photon energy is mainly absorbed by the Cs2AgBiBr6 perovskite layer, generating photogenerated carriers. However, the photogenerated electrons are effectively captured by defect states in the CuAlS2 quantum dot layer, forming carrier capture centers. This suppresses the transmission and separation of effective carriers, reduces the overall conductivity of the photoelectric synaptic device, and ultimately causes the photoelectric synaptic device to exhibit suppressive reverse photoconductive behavior. This enables the optical erasure function of synaptic weights, thereby achieving all-optical memory and erasure functions.
[0028] In some embodiments, the thickness of the electron transport layer is 30nm~150nm, and can be 50nm, 70nm, 90nm, 100nm, 120nm, 140nm, etc., which is beneficial for ZnO to generate sufficient photogenerated carriers while reducing the loss caused by recombination, effectively controlling the migration path of photogenerated carriers, and optimizing the forward photoconductive response performance of the photoelectric synaptic device.
[0029] In some embodiments, the material of the Cs2AgBiBr6 perovskite layer is Cs2AgBiBr6 perovskite material, and the material of the CuAlS2 quantum dot layer is CuAlS2 quantum dot material.
[0030] In some embodiments, the thickness of the composite light-absorbing layer is 215nm~473nm, and can be 220nm, 250nm, 300nm, 350nm, 400nm, 450nm, etc., which is beneficial to balance the thickness of the Cs2AgBiBr6 perovskite layer and the CuAlS2 quantum dot layer. While the Cs2AgBiBr6 perovskite layer provides sufficient photogenerated carriers, the CuAlS2 quantum dot layer fully captures the carriers, thereby suppressing the transmission and separation of effective carriers and reducing the overall conductivity of the photoelectric synaptic device.
[0031] In some embodiments, the thickness of the Cs2AgBiBr6 perovskite layer is 126nm~252nm (e.g., 130nm, 150nm, 180nm, 200nm, 220nm, etc.), and the thickness of the CuAlS2 quantum dot layer is 89nm~221nm (e.g., 90nm, 100nm, 150nm, 175nm, 200nm, etc.).
[0032] By controlling the thickness of the Cs2AgBiBr6 perovskite layer and the CuAlS2 quantum dot layer, it is beneficial for the Cs2AgBiBr6 perovskite layer to generate sufficient photogenerated carriers, while the carriers can be efficiently and fully captured by the CuAlS2 quantum dot layer, thereby achieving effective suppression of the transmission and separation of effective carriers.
[0033] In some embodiments, the ratio of the thickness of the CuAlS2 quantum dot layer to the thickness of the Cs2AgBiBr6 perovskite layer is (0.46~1.07):1, for example, it can be 0.5:1, 0.6:1, 0.8:1, 0.85:1, 0.96:1, 1.05:1, etc.
[0034] By controlling the thickness ratio of the Cs2AgBiBr6 perovskite layer to the CuAlS2 quantum dot layer, it is beneficial to coordinate the generation of photogenerated carriers in the Cs2AgBiBr6 perovskite layer and the capture of photogenerated carriers by the CuAlS2 quantum dot layer, thereby achieving effective suppression of the transmission and separation of effective carriers.
[0035] In some embodiments, the material of the top electrode layer may be Au.
[0036] In some embodiments, the thickness of the top electrode layer can be 60nm to 150nm, for example, it can be 80nm, 100nm, 120nm, 140nm, etc.
[0037] Secondly, the present invention provides a method for fabricating a photoelectric synapse device, comprising: S100, providing basic services.
[0038] S200, an electron transport layer is formed on one side of the base layer.
[0039] S300, A composite light absorption layer is formed on the side of the electron transport layer away from the substrate, and the composite light absorption layer is in contact with the electron transport layer.
[0040] S400, A top electrode layer is formed on the side of the composite light absorption layer away from the electron transport layer, and the top electrode layer is in contact with the composite light absorption layer.
[0041] The composite light absorption layer comprises a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer stacked together. The Cs2AgBiBr6 perovskite layer is in contact with the electron transport layer, and the CuAlS2 quantum dot layer is located on the side of the Cs2AgBiBr6 perovskite layer away from the electron transport layer.
[0042] The method for fabricating a photoelectric synaptic device provided by this invention involves forming a composite light-absorbing layer consisting of a stacked Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer. When 450nm blue light is used as the incident light, the photon energy is effectively and fully absorbed by the Cs2AgBiBr6 perovskite material, generating photogenerated carriers. The photogenerated electrons are efficiently captured by the defect states of the CuAlS2 quantum dot material, forming carrier trapping centers. This effectively suppresses the transmission and separation of effective carriers, reduces the overall conductivity of the photoelectric synaptic device, and enables the photoelectric synaptic device to exhibit suppressive reverse photoconductive behavior, thus realizing the instantaneous light erasure function of the synaptic weight of the photoelectric synaptic device.
[0043] In some embodiments, the substrate may include ITO (indium tin oxide) material; specifically, the substrate may be an ITO glass substrate.
[0044] In some embodiments, an ITO glass substrate cleaned by ultraviolet ozone treatment is used as the base layer.
[0045] In some embodiments, step S200 may include: S210. Electron transport material is deposited on one side of the substrate to form the electron transport layer.
[0046] In some embodiments, the electron transport material may be at least one of ZnO and SnO2. The electron transport material may be deposited on the surface of the substrate. The electron transport material may be deposited by magnetron sputtering.
[0047] In some embodiments, the specific preparation method of the electron transport layer is as follows: a clean ITO glass substrate treated with ultraviolet ozone is transferred to the cavity of a magnetron sputtering coating system, and a ZnO thin film or SnO2 thin film with a thickness of 30 nm to 150 nm is deposited by magnetron sputtering for 3 to 10 minutes at an argon gas pressure of 0.4 Pa to 2 Pa and a radio frequency power of 60 W to 75 W.
[0048] In some embodiments, the stacked Cs2AgBiBr6 perovskite layer and CuAlS2 quantum dot layer can be spin-coated onto the surface of the electron transport layer using an anti-solvent method to form the composite light absorption layer. Specifically, step S300 may include:
[0049] S310 provides Cs2AgBiBr6 precursor solution and CuAlS2 quantum dot dispersion.
[0050] In some embodiments, the preparation step of the Cs2AgBiBr6 precursor solution includes: CsBr, BiBr3 and AgBr are mixed in a molar ratio of 2:(1.0~1.2):(1.0~1.2) in a first solvent and dispersed to obtain the Cs2AgBiBr6 precursor solution.
[0051] Wherein, the first solvent is dimethyl sulfoxide, the dispersion treatment temperature is 55℃~75℃, and the dispersion treatment time is greater than or equal to 12 hours until the solid is completely dissolved.
[0052] In some embodiments, the specific preparation method of Cs2AgBiBr6 precursor solution is as follows: Weigh CsBr, BiBr3 and AgBr in a molar ratio of 2:(1.0~1.2):(1.0~1.2), add 1 mL~3 mL of dimethyl sulfoxide (DMSO), place on a magnetic stirrer and stir at 55 ℃~75 ℃ for more than 12 hours until all chemical powders are dissolved to form Cs2AgBiBr6 precursor solution, seal and place in a glove box for later use.
[0053] In some embodiments, the preparation step of the CuAlS2 quantum dot dispersion includes: CuCl and Al(acac)3 are mixed in a second solvent at a molar ratio of 1:(0.8~1.2), and after degassing, a first mixture is obtained.
[0054] The first mixture was kept at 100℃~160℃ for 30 min~min to obtain the first reaction solution; The first reaction solution is kept at 145℃~160℃ for 15 minutes or more to obtain the second reaction solution; The second reaction solution is mixed with n-dodecyl mercaptan to obtain the third reaction solution; The third reaction solution is mixed with the sulfur precursor solution at 160℃~170℃ for 4 min and then kept at this temperature for 5 min to obtain the fourth reaction solution. The fourth reaction solution is reacted sequentially with the zinc shell precursor solution and the selenium shell precursor solution at 160℃~170℃ to obtain the fifth reaction solution. The fifth reaction solution was kept at 220℃~240℃ for more than or equal to 50 min to obtain CuAlS2 quantum dot stock solution. The CuAlS2 quantum dot stock solution was purified to obtain the CuAlS2 quantum dot dispersion.
[0055] In some embodiments, the second solvent is a mixed solvent of 1-octadecene and oleic acid, wherein the volume ratio of 1-octadecene to oleic acid in the second solvent is 1:(0.8~1.2).
[0056] In some embodiments, the sulfur precursor solution is obtained by dissolving thioacetamide in a third solvent, wherein the third solvent is a mixed solvent of 1-octadecene and n-dodecyl mercaptan, the volume ratio of 1-octadecene to n-dodecyl mercaptan is (6~12):(1.5~4), and the concentration of thioacetamide is 0.00469 g / mL~0.00939 g / mL.
[0057] In some embodiments, the zinc shell precursor solution is obtained by dissolving Zn(St)2 in 1-octadecene, and the concentration of the zinc shell precursor is 0.125 g / mL to 0.188 g / mL.
[0058] In some embodiments, the selenium shell precursor solution is obtained by dissolving Se powder in 1-octadecene, and the concentration of the selenium shell precursor is 0.0131 g / mL to 0.0196 g / mL.
[0059] In some embodiments, the step of purifying the CuAlS2 quantum dot stock solution to obtain the CuAlS2 quantum dot dispersion includes: The CuAlS2 quantum dot stock solution was mixed with the fourth solvent and then subjected to a first centrifugation process to obtain the supernatant.
[0060] The supernatant was mixed with the fifth solvent and then subjected to a second centrifugation process to obtain CuAlS2 quantum dots.
[0061] After drying, the CuAlS2 quantum dots are mixed with a sixth solvent to obtain the CuAlS2 quantum dot dispersion.
[0062] In some embodiments, the fourth solvent is selected from toluene, the fifth solvent is selected from anhydrous ethanol, and the sixth solvent is selected from toluene.
[0063] In some embodiments, the rotation speed of the first centrifugation process is 3000 rpm to 5000 rpm, and the centrifugation time is 3 min to 5 min.
[0064] In some embodiments, the rotation speed of the second centrifugation process is 12000 rpm to 16000 rpm, and the centrifugation time is 5 min to 10 min.
[0065] In some embodiments, the specific preparation method of CuAlS2 quantum dot dispersion is as follows: Weigh CuCl and Al(acac)3 in a molar ratio of 1:(0.8~1.2), and add 6 mL~12 mL of a mixed solution of 1-octadecene (ODE) and oleic acid (OA) (volume ratio 1:(0.8~1.2), second solvent). Then, using a vacuum synthesis line and a magnetically heated stirrer, stir at 400 rpm~600 rpm for at least 60 min at room temperature and under a nitrogen atmosphere to initially remove air and water vapor from the reaction system (degassing treatment). Heat the mixture in the three-necked flask (first mixture) to 100 ℃~160 ℃ and hold for at least 30 min, allowing the solution to gradually turn into a clear, transparent light blue, obtaining the first reaction solution. Then, continue to raise the system temperature to 145 ℃~160 ℃ and hold for at least 15 min to obtain the second reaction solution. After the initial incubation, 3-6 mL of dodecanethiol (DDT) was rapidly injected into the mixed solution (second reaction solution) to induce preliminary nucleation of quantum dots, yielding the third reaction solution. Once the solution (third reaction solution) turned brownish-yellow, it was heated to 160-170℃. Upon reaching the temperature, 0.08-0.12 mL of a sulfur precursor solution (prepared by dissolving 0.0751 g of thioacetamide (TAA) in 6-12 mL of LODE and 1.5-4 mL of DDT, i.e., a TAA concentration of 0.0715 g / mL-0.0939 g / mL) was slowly added dropwise over 4 min using a micro-injection pump to promote further quantum dot growth, yielding the fourth reaction solution. After the addition was complete, the solution was allowed to stand for 5 min, and then 1.5-4 mL of a zinc shell precursor solution and 1.5-3 mL of a selenium shell precursor solution were rapidly injected sequentially to coat the quantum dots with a ZnSe shell, yielding the fifth reaction solution. The zinc shell precursor solution was prepared by dissolving 1.5 g of Zn(St)₂ in 8 mL–12 mL of ODE, and the selenium shell precursor solution was prepared by dissolving 0.157 g of Se powder in 8 mL–12 mL of ODE. After injection, the temperature of the solution (fifth reaction solution) was raised to 220℃–240℃ and maintained for at least 50 min to ensure sufficient ZnSe shell coating. After the reaction, the reaction was quenched using a cold water bath, and the obtained CuAlS₂ quantum dot stock solution was collected for further purification. The purification steps were as follows: 1 mL–2 mL of CuAlS₂ quantum dot stock solution was pipetted and diluted with 3 mL–6 mL of toluene (fourth solvent), then centrifuged at 3000 rpm–5000 rpm for 3 min–5 min to remove impurities. Take the supernatant and add anhydrous ethanol (the fifth solvent) until the total volume of the solution is 10 mL to 15 mL. Mix well to form a CuAlS2 quantum dot suspension.Centrifuge the CuAlS2 quantum dot suspension at 12000 rpm to 16000 rpm for 5 min to 10 min and collect the CuAlS2 quantum dot precipitate. After drying the CuAlS2 quantum dot precipitate, redisperse it in 1 mL to 2 mL of toluene (sixth solvent) to obtain the purified CuAlS2 quantum dot dispersion.
[0066] S320. Preheat treatment of the substrate, the electron transport layer and the Cs2AgBiBr6 precursor solution.
[0067] In some embodiments, the temperature of the preheating treatment is 70°C to 85°C, and the preheating treatment time is 5 min to 10 min.
[0068] S330, the Cs2AgBiBr6 precursor solution forms a Cs2AgBiBr6 precursor layer on the surface of the electron transport layer away from the substrate.
[0069] S340, The CuAlS2 quantum dot dispersion forms a CuAlS2 quantum dot dispersion layer on the surface of the Cs2AgBiBr6 precursor layer away from the electron transport layer.
[0070] S350, heat-treat the Cs2AgBiBr6 precursor layer and the CuAlS2 quantum dot dispersion layer to obtain the composite light absorption layer.
[0071] In some embodiments, the temperature of the heat treatment is 280°C to 320°C, and the time of the heat treatment is 5 min to 10 min.
[0072] In some embodiments, the specific preparation method of the composite light absorption layer can be as follows: place the ZnO / ITO film and the Cs2AgBiBr6 precursor solution on a hot stage and preheat at 70℃~85℃ for 5min-10min. After preheating, place the ZnO / ITO film on a spin coater in a glove box and spin coat it using the anti-solvent method to form a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer. Take 100μL~250μL of 10 mg / mL~30 mg / mL Cs2AgBiBr6 precursor solution and drop it onto the center of the substrate. Then, set the spin coater program to 2000 rpm~4000 rpm and rotate for 50s~60s. At 45 seconds into the spin-coating process, 200 μL–450 μL of a 50 mg / mL–300 mg / mL CuAlS2 quantum dot dispersion was rapidly added dropwise to the center of the substrate. The spin-coated substrate was then placed on a heating stage at 280 °C–320 °C and heated for 5–10 minutes, followed by cooling to room temperature. The resulting composite light-absorbing layer had a thickness of 215 nm–473 nm.
[0073] In some embodiments, toluene in the CuAlS2 quantum dot dispersion is used as the antisolvent of DMSO in the Cs2AgBiBr6 precursor solution to induce Cs2AgBiBr6 nucleation.
[0074] In some embodiments, step S400 includes: S410. The top electrode layer is formed on the surface of the composite light absorption layer away from the electron transport layer using a photomask.
[0075] In some embodiments, the material of the top electrode layer may be Au.
[0076] In some embodiments, the preparation method of the top electrode layer is as follows: the cooled substrate with the composite light absorption layer formed is transferred to the cavity of the magnetron sputtering coating system, argon gas is introduced to maintain the cavity pressure at 0.4 Pa to 2 Pa, and the DC sputtering current is set to 20 mA to 40 mA. An Au electrode with a thickness of 60 nm to 150 nm is deposited on the surface of the Cs2AgBiBr6 perovskite layer by magnetron sputtering through a mask.
[0077] The technical solution of the present invention will be further described in detail below with reference to specific embodiments.
[0078] Example 1 The method for fabricating the photoelectric synaptic device provided in this embodiment includes the following steps: An electron transport layer was prepared by depositing a ZnO layer on an ITO glass substrate using magnetron sputtering. Specifically, a clean ITO glass substrate treated with ultraviolet ozone was transferred into the cavity of a magnetron sputtering coating system, and a 50 nm thick ZnO thin film was deposited by magnetron sputtering for 5 minutes at an argon gas pressure of 2 Pa and a radio frequency power of 75 W.
[0079] A Cs2AgBiBr6 precursor solution and a CuAlS2 quantum dot dispersion were spin-coated onto a ZnO film using an antisolvent method to obtain a composite light-absorbing layer. Specifically, the preparation method of the composite light-absorbing layer consists of three steps: preparation of the Cs2AgBiBr6 perovskite precursor solution, preparation of the CuAlS2 quantum dot dispersion, and preparation of the composite light-absorbing layer.
[0080] The specific preparation method of the Cs2AgBiBr6 precursor solution is as follows: Weigh CsBr, BiBr3 and AgBr in a molar ratio of 2:1:1, add 2 mL of dimethyl sulfoxide (DMSO), place on a magnetic stirrer and stir at 75 °C for more than 12 hours until all chemical powders are dissolved to form the Cs2AgBiBr6 precursor solution, seal and place in a glove box for later use.
[0081] The specific preparation method of CuAlS2 quantum dot dispersion is as follows: Weigh CuCl and Al(acac)3 in a molar ratio of 1:1, and add 10 mL of a mixed solution of 1-octadecene (ODE) and oleic acid (OA) (volume ratio 1:1, second solvent). Then, using a vacuum synthesis line and a magnetically heated stirrer, stir at 500 rpm for at least 60 min at room temperature under a nitrogen atmosphere to initially remove air and water vapor from the reaction system (degassing treatment). Heat the mixture in the three-necked flask (first mixture) to 120℃ and hold for at least 30 min, allowing the solution to gradually turn into a clear, transparent light blue, obtaining the first reaction solution. Then, continue to raise the system temperature to 150℃ and hold for at least 15 min to obtain the second reaction solution. After the holding period, rapidly inject 5 mL of n-dodecyl mercaptan (DDT) into the mixed solution (second reaction solution) to induce preliminary nucleation of quantum dots, obtaining the third reaction solution. Once the solution (third reaction solution) turns brownish-yellow, heat it to 170℃. After reaching the set temperature, 0.1 mL of a sulfur precursor solution (prepared by dissolving 0.0751 g of thioacetamide (TAA) in 6 mL of ODE and 2 mL of DDT, i.e., TAA concentration of 0.00939 g / mL) was slowly added dropwise over 4 min using a micro-injection pump to promote further growth of quantum dots, yielding the fourth reaction solution. After the addition was complete, the mixture was allowed to stand for 5 min, and then 3 mL of a zinc shell precursor solution and 2 mL of a selenium shell precursor solution were rapidly injected sequentially to coat the quantum dots with a ZnSe shell, yielding the fifth reaction solution. The zinc shell precursor solution was prepared by dissolving 1.5 g of Zn(St)₂ in 10 mL of ODE (concentration of 0.15 g / mL), and the selenium shell precursor solution was prepared by dissolving 0.157 g of Se powder in 10 mL of ODE (concentration of 0.0157 g / mL). After injection, the temperature of the solution (fifth reaction solution) was raised to 230 ℃ and maintained for at least 50 min to ensure sufficient ZnSe shell coating. After the reaction, the reaction was quenched using a cold water bath, and the obtained CuAlS2 quantum dot stock solution was collected for further purification. The purification steps are as follows: 1 mL of CuAlS2 quantum dot stock solution was taken with a dropper, diluted with 5 mL of toluene (fourth solvent), and then centrifuged at 3000 rpm for 5 min to remove impurities. The supernatant was collected, and anhydrous ethanol (fifth solvent) was added to a total solution volume of 10 mL. After mixing thoroughly, a CuAlS2 quantum dot suspension was formed. The CuAlS2 quantum dot suspension was centrifuged at 12000 rpm for 5 min, and the CuAlS2 quantum dot precipitate was collected. After drying the CuAlS2 quantum dot precipitate, it was redispersed in 1 mL of toluene (sixth solvent) to obtain the purified CuAlS2 quantum dot dispersion.
[0082] The specific preparation method of the composite light absorption layer is as follows: place the ZnO / ITO film and the Cs2AgBiBr6 precursor solution on a hot stage and preheat at 75 °C for 10 min. After preheating, place the ZnO / ITO film on a spin coater in a glove box and spin coat it using the anti-solvent method to form a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer. Take 200 μL of 20 mg / mL Cs2AgBiBr6 precursor solution and drop it onto the center of the substrate. Then, set the spin coater program to rotate at 3000 rpm for 60 s. At 45 s during the spin coating process, 300 μL of a 100 mg / mL CuAlS2 quantum dot dispersion was rapidly added to the center of the substrate. Finally, the spin-coated substrate was placed on a heating stage at 300 ℃ and heated for 10 min, and then cooled to room temperature. The resulting composite light absorption layer had a thickness of 362 nm, of which the Cs2AgBiBr6 perovskite layer had a thickness of 185 nm and the CuAlS2 quantum dot layer had a thickness of 177 nm.
[0083] Electrodes were obtained by magnetron sputtering gold onto a CuAlS2 quantum dot layer. Specifically, the cooled substrate with the composite light-absorbing layer formed was transferred to the cavity of the magnetron sputtering coating system. Argon gas was introduced to maintain the cavity pressure at 2 Pa, and the DC sputtering current was set to 20 mA. An Au electrode with a thickness of 100 nm was deposited on the surface of the CuAlS2 quantum dot layer by magnetron sputtering through a mask, thereby obtaining a photoelectric synaptic device.
[0084] Example 2 The method for fabricating the photoelectric synaptic device provided in this embodiment includes the following steps: An electron transport layer was prepared by depositing a ZnO layer on an ITO glass substrate using magnetron sputtering. Specifically, a clean ITO glass substrate treated with ultraviolet ozone was transferred into the cavity of a magnetron sputtering coating system, and a 50 nm thick ZnO thin film was deposited by magnetron sputtering for 3 minutes at an argon gas pressure of 0.4 Pa and a radio frequency power of 60 W.
[0085] A Cs2AgBiBr6 precursor solution and a CuAlS2 quantum dot dispersion were spin-coated onto a ZnO film using an antisolvent method to obtain a composite light-absorbing layer. Specifically, the preparation method of the composite light-absorbing layer consists of three steps: preparation of the Cs2AgBiBr6 perovskite precursor solution, preparation of the CuAlS2 quantum dot dispersion, and preparation of the composite light-absorbing layer.
[0086] The specific preparation method of Cs2AgBiBr6 precursor solution is as follows: Weigh CsBr, BiBr3 and AgBr in a molar ratio of 2:1.1:1.1, add them to 1 mL of dimethyl sulfoxide (DMSO), place them on a magnetic stirrer and stir at 55 °C for more than 12 hours until all chemical powders are dissolved to form Cs2AgBiBr6 precursor solution, seal it and place it in a glove box for later use.
[0087] The specific preparation method of CuAlS2 quantum dot dispersion is as follows: CuCl and Al(acac)3 with a molar ratio of 1:0.8 are weighed, and 6 mL of a mixed solution of 1-octadecene (ODE) and oleic acid (OA) (volume ratio 1:0.8, second solvent) is added. Subsequently, the mixture is stirred at 400 rpm for at least 60 min at room temperature under a nitrogen atmosphere using a vacuum synthesis line and a magnetically heated stirrer to initially remove air and water vapor from the reaction system (degassing treatment). The mixture in the three-necked flask (first mixture) is heated to 100 °C and held for at least 30 min, allowing the solution to gradually turn into a clear, transparent light blue, obtaining the first reaction solution. Then, the system temperature is further increased to 145 °C and held for at least 15 min to obtain the second reaction solution. After the holding time is complete, 3 mL of n-dodecyl mercaptan (DDT) is rapidly injected into the mixed solution (second reaction solution) to induce preliminary nucleation of quantum dots, obtaining the third reaction solution. Once the solution (third reaction solution) turns brownish-yellow, it is heated to 165 °C. After reaching the desired temperature, 0.08 mL of a sulfur precursor solution (prepared by dissolving 0.0751 g of thioacetamide (TAA) in 12 mL of ODE and 4 mL of DDT, i.e., TAA concentration of 0.00469 g / mL) was slowly added dropwise over 4 min using a micro-injection pump to promote further growth of quantum dots, yielding the fourth reaction solution. After the addition was complete, the mixture was allowed to stand for 5 min, and then 2.5 mL of a zinc shell precursor solution and 1.5 mL of a selenium shell precursor solution were rapidly injected sequentially to coat the quantum dots with a ZnSe shell, yielding the fifth reaction solution. The zinc shell precursor solution was prepared by dissolving 1.5 g of Zn(St)₂ in 12 mL of ODE (concentration of 0.125 g / mL), and the selenium shell precursor solution was prepared by dissolving 0.157 g of Se powder in 8 mL of ODE (concentration of 0.0196 g / mL). After injection, the temperature of the solution (fifth reaction solution) was raised to 220 ℃ and maintained for at least 50 min to ensure sufficient ZnSe shell coating. After the reaction, the reaction was quenched using a cold water bath, and the obtained CuAlS2 quantum dot stock solution was collected for further purification. The purification steps are as follows: 1.5 mL of CuAlS2 quantum dot stock solution was taken with a dropper, diluted with 3 mL of toluene (fourth solvent), and then centrifuged at 4000 rpm for 3 min to remove impurities. The supernatant was collected, and anhydrous ethanol (fifth solvent) was added to a total solution volume of 12 mL. After mixing thoroughly, a CuAlS2 quantum dot suspension was formed. The CuAlS2 quantum dot suspension was centrifuged at 13000 rpm for 7 min, and the CuAlS2 quantum dot precipitate was collected. After drying the CuAlS2 quantum dot precipitate, it was redispersed in 1.5 mL of toluene (sixth solvent) to obtain the purified CuAlS2 quantum dot dispersion.
[0088] The specific preparation method of the composite light absorption layer is as follows: place the ZnO / ITO film and the Cs2AgBiBr6 precursor solution on a hot stage and preheat at 70 ℃ for 5 min. After preheating, place the ZnO / ITO film on a spin coater in a glove box and spin coat it using the anti-solvent method to form a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer. Take 100 μL of 15 mg / mL Cs2AgBiBr6 precursor solution and drop it onto the center of the substrate. Then, set the spin coater program to 2000 rpm for 50 s. At 45 s during the spin coating process, 200 μL of a 100 mg / mL CuAlS2 quantum dot dispersion was rapidly added to the center of the substrate. Finally, the spin-coated substrate was placed on a heating stage at 280 ℃ and heated for 5 min, and then cooled to room temperature. The resulting composite light absorption layer had a thickness of 314 nm, of which the Cs2AgBiBr6 perovskite layer had a thickness of 152 nm and the CuAlS2 quantum dot layer had a thickness of 162 nm.
[0089] Electrodes were obtained by magnetron sputtering gold onto a CuAlS2 quantum dot layer. Specifically, the cooled substrate with the composite light-absorbing layer formed was transferred to the cavity of the magnetron sputtering coating system. Argon gas was introduced to maintain the cavity pressure at 0.4 Pa, and the DC sputtering current was set to 30 mA. An Au electrode with a thickness of 60 nm was deposited on the surface of the CuAlS2 quantum dot layer by magnetron sputtering through a mask.
[0090] Example 3 The method for fabricating the photoelectric synaptic device provided in this embodiment includes the following steps: An electron transport layer was prepared by depositing a ZnO layer on an ITO glass substrate using magnetron sputtering. Specifically, a clean ITO glass substrate treated with ultraviolet ozone was transferred into the cavity of a magnetron sputtering coating system, and a 50 nm thick ZnO thin film was deposited by magnetron sputtering for 10 minutes at an argon gas pressure of 1 Pa and a radio frequency power of 70 W.
[0091] A Cs2AgBiBr6 precursor solution and a CuAlS2 quantum dot dispersion were spin-coated onto a ZnO film using an antisolvent method to obtain a composite light-absorbing layer. Specifically, the preparation method of the composite light-absorbing layer consists of three steps: preparation of the Cs2AgBiBr6 perovskite precursor solution, preparation of the CuAlS2 quantum dot dispersion, and preparation of the composite light-absorbing layer.
[0092] The specific preparation method of Cs2AgBiBr6 precursor solution is as follows: Weigh CsBr, BiBr3 and AgBr in a molar ratio of 2:1.2:1.2, add them to 3 mL of dimethyl sulfoxide (DMSO), place them on a magnetic stir bar and stir at 65 °C for more than 12 hours until all chemical powders are dissolved to form Cs2AgBiBr6 precursor solution, seal it and place it in a glove box for later use.
[0093] The specific preparation method of CuAlS2 quantum dot dispersion is as follows: CuCl and Al(acac)3 with a molar ratio of 1:1.2 are weighed, and 10 mL of a mixed solution of 1-octadecene (ODE) and oleic acid (OA) (volume ratio 1:1.2, second solvent) is added. Subsequently, the mixture is stirred at 600 rpm for at least 60 min at room temperature under a nitrogen atmosphere using a vacuum synthesis line and a magnetically heated stirrer to initially remove air and water vapor from the reaction system (degassing treatment). The mixture in the three-necked flask (first mixture) is heated to 160 °C and held for at least 30 min, allowing the solution to gradually turn into a clear, transparent light blue, obtaining the first reaction solution. Then, the system temperature is further increased to 160 °C and held for at least 15 min to obtain the second reaction solution. After the holding period, 6 mL of n-dodecyl mercaptan (DDT) is rapidly injected into the mixed solution (second reaction solution) to induce preliminary nucleation of quantum dots, obtaining the third reaction solution. After the solution (third reaction solution) turns brownish-yellow, it is heated to 160 °C. Once the temperature is reached, 0.12 mL of sulfur precursor solution (prepared by dissolving 0.0751 g of thioacetamide (TAA) in 7 mL of ODE and 1.5 mL of DDT, i.e., TAA concentration of 0.00884 g / mL) is slowly added dropwise over 5 min using a micro-injection pump to promote further growth of quantum dots, resulting in the fourth reaction solution. After the addition is complete, the solution is allowed to stand for 5 min, and then 4 mL of zinc shell precursor solution and 3 mL of selenium shell precursor solution are rapidly injected sequentially to coat the quantum dots with a ZnSe shell, resulting in the fifth reaction solution. The zinc shell precursor solution was prepared by dissolving 1.5 g of Zn(St)₂ in 8 mL of ODE (concentration: 0.188 g / mL), and the selenium shell precursor solution was prepared by dissolving 0.157 g of Se powder in 12 mL of ODE (concentration: 0.0131 g / mL). After injection, the solution (fifth reaction solution) was heated to 240 ℃ and kept at that temperature for at least 50 min to ensure sufficient ZnSe shell coating. After the reaction, the reaction was quenched using a cold water bath, and the obtained CuAlS₂ quantum dot stock solution was collected for further purification. The purification steps were as follows: 2 mL of CuAlS₂ quantum dot stock solution was taken with a dropper, diluted with 6 mL of toluene (fourth solvent), and then centrifuged at 5000 rpm for 5 min to remove impurities. The supernatant was taken, and anhydrous ethanol (fifth solvent) was added to a total solution volume of 15 mL. After mixing thoroughly, a CuAlS₂ quantum dot suspension was formed. The CuAlS2 quantum dot suspension was centrifuged at 16,000 rpm for 10 min, and the CuAlS2 quantum dot precipitate was collected. After drying the CuAlS2 quantum dot precipitate, it was redispersed in 2 mL of toluene (the sixth solvent) to obtain the purified CuAlS2 quantum dot dispersion.
[0094] The specific preparation method of the composite light absorption layer is as follows: place the ZnO / ITO film and the Cs2AgBiBr6 precursor solution on a hot stage and preheat at 85 °C for 7.5 min. After preheating, place the ZnO / ITO film on a spin coater in a glove box and spin coat it using the anti-solvent method to form a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer. Take 250 μL of 25 mg / mL Cs2AgBiBr6 precursor solution and drop it onto the center of the substrate. Then, set the spin coater program to 4000 rpm for 60 s. At 45 s during the spin coating process, 450 μL of a 120 mg / mL CuAlS2 quantum dot dispersion was rapidly added to the center of the substrate. Finally, the spin-coated substrate was placed on a heating stage at 320 ℃ and heated for 10 min, and then cooled to room temperature. The resulting composite light absorption layer had a thickness of 414 nm, of which the Cs2AgBiBr6 perovskite layer had a thickness of 221 nm and the CuAlS2 quantum dot layer had a thickness of 193 nm.
[0095] Electrodes were obtained by magnetron sputtering gold onto a CuAlS2 quantum dot layer. Specifically, the cooled substrate with the composite light absorption layer formed was transferred to the cavity of the magnetron sputtering coating system. Argon gas was introduced to maintain the cavity pressure at 2 Pa, and the DC sputtering current was set to 40 mA. An Au electrode with a thickness of 150 nm was deposited on the surface of the CuAlS2 quantum dot layer by magnetron sputtering through a mask.
[0096] Example 4 This embodiment is similar to Embodiment 1, except that the thickness of the composite light-absorbing layer is 473 nm. The specific preparation method of the composite light absorption layer is as follows: place the ZnO / ITO film and the Cs2AgBiBr6 precursor solution on a hot stage and preheat at 75 ℃ for 10 min. After preheating, place the ZnO / ITO film on a spin coater in a glove box and spin coat it using the anti-solvent method to form a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer. Take 200 μL of 30 mg / mL Cs2AgBiBr6 precursor solution and drop it onto the center of the substrate. Then, set the spin coater program to rotate at 3000 rpm for 60 s. At 45 s during the spin coating process, 300 μL of a 300 mg / mL CuAlS2 quantum dot dispersion was rapidly added to the center of the substrate. Finally, the spin-coated substrate was placed on a heating stage at 300 ℃ and heated for 10 min, and then cooled to room temperature. The resulting composite light absorption layer had a thickness of 473 nm, of which the Cs2AgBiBr6 perovskite layer had a thickness of 252 nm and the CuAlS2 quantum dot layer had a thickness of 221 nm.
[0097] Example 5 This embodiment is similar to Embodiment 1, except that the thickness of the composite light-absorbing layer is 215 nm. The specific preparation method of the composite light absorption layer is as follows: place the ZnO / ITO film and the Cs2AgBiBr6 precursor solution on a hot stage and preheat at 75 ℃ for 10 min. After preheating, place the ZnO / ITO film on a spin coater in a glove box and spin coat it using the anti-solvent method to form a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer. Take 200 μL of 10 mg / mL Cs2AgBiBr6 precursor solution and drop it onto the center of the substrate. Then set the spin coater program to 3000 rpm for 60 s. At 45 s during the spin coating process, 300 μL of a 50 mg / mL CuAlS2 quantum dot dispersion was rapidly added to the center of the substrate. Finally, the spin-coated substrate was placed on a heating stage at 300 ℃ and heated for 10 min, and then cooled to room temperature. The resulting composite light absorption layer had a thickness of 215 nm, of which the Cs2AgBiBr6 perovskite layer had a thickness of 126 nm and the CuAlS2 quantum dot layer had a thickness of 89 nm.
[0098] Example 6 This embodiment is similar to Embodiment 1, except that the thickness of the Cs2AgBiBr6 perovskite layer is 185 nm and the thickness of the CuAlS2 quantum dot layer is 86 nm. The specific preparation method of the composite light absorption layer is as follows: place the ZnO / ITO film and the Cs2AgBiBr6 precursor solution on a hot stage and preheat at 75 °C for 10 min. After preheating, place the ZnO / ITO film on a spin coater in a glove box and spin coat it using the anti-solvent method to form a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer. Take 200 μL of 20 mg / mL Cs2AgBiBr6 precursor solution and drop it onto the center of the substrate. Then, set the spin coater program to rotate at 3000 rpm for 60 s. At 45 s during the spin coating process, 300 μL of a 50 mg / mL CuAlS2 quantum dot dispersion was rapidly added to the center of the substrate. Finally, the spin-coated substrate was placed on a heating stage at 300 ℃ and heated for 10 min, and then cooled to room temperature. The resulting composite light absorption layer had a thickness of 271 nm, of which the Cs2AgBiBr6 perovskite layer had a thickness of 185 nm and the CuAlS2 quantum dot layer had a thickness of 86 nm.
[0099] Example 7 This embodiment is similar to Embodiment 1, except that the thickness of the Cs2AgBiBr6 perovskite layer is 187 nm and the thickness of the CuAlS2 quantum dot layer is 221 nm. The specific preparation method of the composite light absorption layer is as follows: place the ZnO / ITO film and the Cs2AgBiBr6 precursor solution on a hot stage and preheat at 75 °C for 10 min. After preheating, place the ZnO / ITO film on a spin coater in a glove box and spin coat it using the anti-solvent method to form a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer. Take 200 μL of 20 mg / mL Cs2AgBiBr6 precursor solution and drop it onto the center of the substrate. Then, set the spin coater program to rotate at 3000 rpm for 60 s. At 45 s during the spin coating process, 300 μL of a 300 mg / mL CuAlS2 quantum dot dispersion was rapidly added dropwise to the center of the substrate. Finally, the spin-coated substrate was placed on a heating stage at 300 ℃ and heated for 10 min, and then cooled to room temperature. The resulting composite light absorption layer had a thickness of 408 nm, of which the Cs2AgBiBr6 perovskite layer had a thickness of 187 nm and the CuAlS2 quantum dot layer had a thickness of 221 nm.
[0100] Example 8 This embodiment is similar to Embodiment 1, except that the thickness of the ZnO film is 30 nm. An electron transport layer was prepared by depositing a ZnO layer on an ITO glass substrate using magnetron sputtering. Specifically, a clean ITO glass substrate treated with ultraviolet ozone was transferred into the cavity of a magnetron sputtering coating system, and a 30 nm thick ZnO thin film was deposited by magnetron sputtering for 5 minutes at an argon gas pressure of 2 Pa and a radio frequency power of 75 W.
[0101] Example 9 This embodiment is similar to Embodiment 1, except that the thickness of the ZnO film is 150 nm. An electron transport layer was prepared by depositing a ZnO layer on an ITO glass substrate using magnetron sputtering. Specifically, a clean ITO glass substrate treated with ultraviolet ozone was transferred into the cavity of a magnetron sputtering coating system, and a 150 nm thick ZnO thin film was deposited by magnetron sputtering for 5 minutes at an argon gas pressure of 2 Pa and a radio frequency power of 75 W.
[0102] Example 10 This embodiment is similar to Embodiment 1, except that SnO2 material is used as the electron transport layer: An electron transport layer was prepared by depositing a SnO2 layer on an ITO glass substrate using magnetron sputtering. Specifically, a clean ITO glass substrate treated with ultraviolet ozone was transferred into the cavity of a magnetron sputtering coating system, and a 50 nm thick thin film was deposited by magnetron sputtering for 5 minutes at an argon gas pressure of 2 Pa and a radio frequency power of 75 W.
[0103] Comparative Example 1 This comparative example is similar to Example 1, except that: The photoelectric synaptic device in this comparative example does not have a CuAlS2 quantum dot layer, but the other film structure and preparation method are the same as in Example 1.
[0104] Comparative Example 2 This comparative example is similar to Example 1, except that: The photoelectric synaptic device in this comparative example does not have a ZnO layer, but the other film structure and preparation method are the same as in Example 1.
[0105] Comparative Example 3 This comparative example is similar to Example 1, except that: In the preparation of the composite light-absorbing layer, 200 μL of a Cs2AgBiBr6 precursor solution with a concentration of 40 mg / mL and 300 μL of a CuAlS2 quantum dot dispersion with a concentration of 400 mg / mL were used to make the thickness of the composite light-absorbing layer 621 nm, wherein the thickness of the Cs2AgBiBr6 perovskite layer was 347 nm and the thickness of the CuAlS2 quantum dot layer was 274 nm.
[0106] Comparative Example 4 This comparative example provides a photoelectric synapse device, including the following fabrication steps: 25 mL of glycerol was added to a clean weighing bottle as the substrate for crystal growth. Then, 50 µL of a solution of n-type 2,2'-((5Z,5'Z)-5,5'-(furan-2,5-diylidene)bis(4-octylthiophene-5,2(5H)-diylidene)) dimalonitrile (TFT-CN) and a p-type π-conjugated dithiophene[3,2-b:2',3'-d]thiophene derivative (DTT-8) (1 mg / mL, chlorobenzene as solvent) were mixed with sodium perfluorooctanoate (0.001 mg / mL) and drop-coated onto the glycerol surface. After the solvent evaporated, two-dimensional molecular crystals of TFT-CN (2DMC) or DTT-8 floating on the glycerol surface were obtained. Using SiO2 (300 nm) / Si wafers as substrates, the wafers were ultrasonically cleaned sequentially with deionized water, acetone, and isopropanol for 10 minutes each, followed by oxygen plasma treatment. A PMMA solution (3 mg / mL, chlorobenzene as solvent) was then spin-coated onto the substrate and annealed at 120°C for 10 minutes. Afterward, the substrate was inverted and immersed in glycerol, and the DTT-8 crystal was retrieved and transferred to a SiO2 / Si substrate. The substrate was then washed with deionized water. Finally, a TFT-CN crystal was transferred onto the substrate covered with the DTT-8 crystal to form a pn heterojunction. Two Ag (80 nm) / Au (80 nm) strip films were pressed onto the 2DMC pn heterojunction as the drain and source, respectively, and an OFET device was constructed using a bottom-gate top-contact configuration.
[0107] Comparative Example 5 This comparative example provides a photoelectric synapse device, including the following fabrication steps: Amorphous IGZO films with a diameter of 100 µm were deposited on Pt / Ti / SiO2 / Si, SiO2 / Si, and quartz substrates at room temperature using radio frequency magnetron sputtering with an in-situ metal mask. The sputtering target was a 99.99% pure InGaZnO4 ceramic target (In2O3:Ga4O5:ZnO = 1:1:2 molar ratio), with a sputtering power of 60 W and a gas pressure of 0.5 Pa. OD-IGZO was sputtered in a pure Ar atmosphere, while OR-IGZO was deposited in a mixed atmosphere of Ar and O2 (partial pressure ratio of 1:1). The thickness of both OD-IGZO and OR-IGZO films was 30 nm. Au top electrodes with a diameter of 100 µm and a thickness of 10 nm were deposited on OD-IGZO, OR-IGZO, and OD-IGZO / OR-IGZO composite films at room temperature using electron beam evaporation with an in-situ metal mask. Radio frequency magnetron sputtering was used to deposit an ITO electrode with a thickness of 30 nm and a diameter of 100 µm at room temperature using a 99.99% pure ITO ceramic target (In2O3:SnO2 = 5:1, molar ratio) and an in-situ metal mask. The sputtering atmosphere was Ar, the sputtering power was 40 W, and the gas pressure was 0.5 Pa.
[0108] Comparative Example 6 This comparative example is similar to Example 1, except that: In the preparation of the composite light-absorbing layer, 100 μL of a 10 mg / mL Cs2AgBiBr6 precursor solution and 100 μL of a 50 mg / mL CuAlS2 quantum dot dispersion were used to make the thickness of the composite light-absorbing layer 100 nm, wherein the thickness of the Cs2AgBiBr6 perovskite layer was 73 nm and the thickness of the CuAlS2 quantum dot layer was 27 nm.
[0109] Comparative Example 7 This comparative example is similar to Example 1, except that: The specific preparation method of the composite light absorption layer is as follows: place the ZnO / ITO film and the Cs2AgBiBr6 precursor solution on a hot stage and preheat at 75 °C for 10 min. After preheating, place the ZnO / ITO film on a spin coater in a glove box and spin coat it using the anti-solvent method to form a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer. Take 200 μL of 20 mg / mL Cs2AgBiBr6 precursor solution and drop it onto the center of the substrate. Then, set the spin coater program to rotate at 3000 rpm for 60 s. At 45 s during the spin coating process, 300 μL of a 30 mg / mL CuAlS2 quantum dot dispersion was rapidly added to the center of the substrate. Finally, the spin-coated substrate was placed on a heating stage at 300 ℃ and heated for 10 min, and then cooled to room temperature. The resulting composite light-absorbing layer had a thickness of 200 nm, of which the Cs2AgBiBr6 perovskite layer had a thickness of 162 nm and the CuAlS2 quantum dot layer had a thickness of 38 nm.
[0110] Comparative Example 8 This comparative example is similar to Example 1, except that: The specific preparation method of the composite light absorption layer is as follows: place the ZnO / ITO film and the Cs2AgBiBr6 precursor solution on a hot stage and preheat at 75 °C for 10 min. After preheating, place the ZnO / ITO film on a spin coater in a glove box and spin coat it using the anti-solvent method to form a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer. Take 200 μL of 20 mg / mL Cs2AgBiBr6 precursor solution and drop it onto the center of the substrate. Then, set the spin coater program to rotate at 3000 rpm for 60 s. At 45 s during the spin coating process, 300 μL of a 350 mg / mL CuAlS2 quantum dot dispersion was rapidly added to the center of the substrate. Finally, the spin-coated substrate was placed on a heating stage at 300 ℃ and heated for 10 min, and then cooled to room temperature. The resulting composite light absorption layer had a thickness of 400 nm, of which the Cs2AgBiBr6 perovskite layer had a thickness of 167 nm and the CuAlS2 quantum dot layer had a thickness of 233 nm.
[0111] The photoelectric synaptic devices obtained in the above embodiments and comparative examples were subjected to performance tests: a Keithley 4200 digital source meter was used to test the photoelectric performance of the sample from the embodiments, and the results are as follows. Figure 3 (a)~3(c) Figures 4-5 As shown in Table 1.
[0112] Table 1. Photoelectric performance test results of the examples and comparative examples like Figure 1 As shown, in the photoelectric synapse device obtained in Example 1, a composite light absorption layer and an electron transport layer are stacked. Along the direction from the electron transport layer to the composite light absorption layer, a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer are sequentially stacked. The transmission electron microscopy results of the CuAlS2 quantum dots in the CuAlS2 quantum dot layer are shown below. Figure 2 As shown in the figure, the clear spherical morphology and lattice fringes of the quantum dots can be observed, indicating that they have good crystallinity. The lattice fringes of a single quantum dot were measured, and the interplanar spacing was found to be about 3.8 Å. This spacing is highly matched with the (111) interplanar spacing of the zincblende (ZB) structure ZnSe, directly confirming that the ZnSe shell has been successfully coated on the surface of the quantum dots.
[0113] Among them, such as Figure 3 As shown in (a) to 3(c), the photoelectric synaptic device obtained in Example 1 operates at a wavelength of 380 nm and a power density of 4.61 mW / cm². 2 Under photoexcitation with a pulse width of 10 s, the photosynaptic device exhibits significant two-pulse facilitator (PPF) characteristics with a PPF exponent of 118% at a voltage bias of -0.15 V. Furthermore, it can transition from short-term plasticity to long-term enhancement by increasing the stimulation time or number of stimulations. Figure 4 As shown, the photoelectric synapse device obtained in Example 1 operates at a wavelength of 450 nm and a power density of 5.87 mW / cm². 2 Under illumination, the photosynaptic device exhibits significant current suppression at a voltage bias of -0.15 V, and the device's photoresponse rise time is [not specified]. τ r ( τ r The time required for the photocurrent to rise from 10% to its maximum value (where the photocurrent response is negative) is 62.8 ms, and the decay time is... τ f ( τ f The time required for the photocurrent to decrease from 90% of its maximum value to 10% is 157.4 ms, significantly faster than the response speed at 380 nm. Figure 5As shown, the photoelectric synapse device obtained in Example 1 exhibits a slow increase in current at 380 nm and a rapid decrease after 450 nm illumination when alternately illuminated with 380 nm and 450 nm light. The photoelectric synapse device demonstrates fully optically controlled "writing" and "erasing" effects. That is, when excited by 380 nm light, the ZnO layer generates a large number of photogenerated carriers, effectively reducing the probability of charge recombination, resulting in a positive photoconductivity enhancement effect consistent with the characteristics of excitatory synapses. However, under 450 nm illumination, photoexcitation mainly originates from the Cs2AgBiBr6 perovskite layer, and the generated photogenerated carriers are captured by defect states in the CuAlS2 quantum dot layer during transport, leading to a significant decrease in the overall conductivity of the photoelectric synapse device.
[0114] The photoelectric synaptic device obtained in Comparative Example 1, with an excitation wavelength of 380 nm, a pulse width of 10 s, and a power density of 4.61 mW / cm², performs well. 2 When a bias voltage of -0.15 V is applied, the device exhibits positive memristor characteristics with a PPF index of 108%. At an excitation wavelength of 450 nm, a pulse width of 10 s, and a power density of 5.87 mW / cm², the device also demonstrates this characteristic. 2 When a bias voltage of -0.15 V is applied, the device also exhibits positive memristor characteristics with a PPF index of 105%.
[0115] The photoelectric synaptic device obtained in Comparative Example 2, with an excitation wavelength of 380 nm, a pulse width of 10 s, and a power density of 4.61 mW / cm², 2 When a bias voltage of -0.15 V is applied, the device exhibits a negative response but does not display memristor characteristics. The photoexcitation wavelength is 450 nm, the pulse width is 10 s, and the power density is 5.87 mW / cm². 2 When a bias voltage of -0.15 V is applied, the device also exhibits a negative response.
[0116] The photoelectric synapse device obtained in Comparative Example 3, with an excitation wavelength of 380 nm, a pulse width of 10 s, and a power density of 4.61 mW / cm², performs well. 2 When a bias voltage of -0.15 V is applied, the device exhibits positive memristor characteristics with a PPF index of 115%. The device also performs well under light excitation at a wavelength of 450 nm, a pulse width of 10 s, and a power density of 5.87 mW / cm². 2 When a bias voltage of -0.15 V is applied, the device exhibits a negative response, but the rise time and decay time are extended to 81.7 ms and 185.78 ms, respectively.
[0117] The photoelectric synapse device obtained in Comparative Example 4, fabricated from bottom to top, is a bimodal photosynapse constructed using a Si / SiO2 / PMMA / light absorption layer / Ag electrode structure. It exhibits positive and negative memristor responses under bias voltages of -15 V and 60 V, respectively. The negative current decreases slowly with illumination, failing to achieve an immediate erasing effect.
[0118] The photoelectric synaptic device obtained in Comparative Example 5, with an incident light power density of 20 µW / cm², 2 At that time, the device exhibits a positive memristor response under blue light and a negative memristor response under near-infrared light, and thus cannot achieve an instant erasure effect.
[0119] Comparing the photoelectric synapse devices obtained in the above embodiments with those obtained in Comparative Example 1, it can be seen that CuAlS2 provides negative response capability; comparing the photoelectric synapse devices obtained in the above embodiments with those obtained in Comparative Example 2, it can be seen that ZnO provides memristor effect; comparing the photoelectric synapse devices obtained in the above embodiments with those obtained in Comparative Examples 3 and 6, it can be seen that the thickness of the composite light absorption layer affects the photoelectric performance of the photoelectric synapse device, and controlling the thickness of the composite light absorption layer to 215nm~473nm is more conducive to obtaining photoelectric synapse devices with improved overall performance; comparing the photoelectric synapse devices obtained in the above embodiments with those obtained in Comparative Examples 7 and 8, it can be seen that CuAlS2 provides negative response capability; comparing the photoelectric synapse devices obtained in the above embodiments with those obtained in Comparative Examples 7 and 8, it can be seen that CuAlS2 provides negative response capability; comparing the photoelectric synapse devices obtained in the above embodiments with those obtained in Comparative Examples 2 and 3 ... Comparison of synaptic devices shows that controlling the thickness of the Cs2AgBiBr6 perovskite layer to be 126nm~252nm, the thickness of the CuAlS2 quantum dot layer to be 89nm~221nm, and the ratio of the thickness of the CuAlS2 quantum dot layer to the thickness of the Cs2AgBiBr6 perovskite layer to be (0.46~1.07):1 is more conducive to obtaining photoelectric synaptic devices with improved overall performance. Comparison of the photoelectric synaptic devices obtained in the above embodiments with those obtained in Comparative Examples 4 and 5 shows that the composite light absorption layer constructed by combining Cs2AgBiBr6 / CuAlS2 can effectively realize the optical memory and erasure functions of the photoelectric synaptic device.
[0120] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A photoelectric synapse device, characterized in that, include: grassroots level; An electron transport layer is located on one side of the base layer; A composite light absorption layer is located on the side of the electron transport layer away from the base layer, and the composite light absorption layer is in contact with the electron transport layer; A top electrode layer is located on the side of the composite light absorption layer away from the electron transport layer, and the top electrode layer is in contact with the composite light absorption layer; The composite light absorption layer comprises a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer stacked together. The Cs2AgBiBr6 perovskite layer is in contact with the electron transport layer, and the CuAlS2 quantum dot layer is located on the side of the Cs2AgBiBr6 perovskite layer away from the electron transport layer.
2. The photoelectric synapse device as described in claim 1, characterized in that: The electron transport layer is selected from at least one of ZnO and SnO2 materials; The thickness of the electron transport layer is 30nm~150nm.
3. The photoelectric synapse device as described in claim 1, characterized in that: The Cs2AgBiBr6 perovskite layer is made of Cs2AgBiBr6 perovskite material, and the CuAlS2 quantum dot layer is made of CuAlS2 quantum dot material. The thickness of the composite light-absorbing layer is 215nm~473nm, the thickness of the Cs2AgBiBr6 perovskite layer is 126nm~252nm, and the thickness of the CuAlS2 quantum dot layer is 89nm~221nm. The thickness ratio of the CuAlS2 quantum dot layer to the Cs2AgBiBr6 perovskite layer is (0.46~1.07):
1.
4. A method for fabricating a photoelectric synaptic device, characterized in that, include: Provide for the grassroots; An electron transport layer is formed on one side of the base layer; A composite light absorption layer is formed on the side of the electron transport layer away from the base layer, and the composite light absorption layer is in contact with the electron transport layer; A top electrode layer is formed on the side of the composite light absorption layer away from the electron transport layer, and the top electrode layer is in contact with the composite light absorption layer; The composite light absorption layer comprises a Cs2AgBiBr6 perovskite layer and a CuAlS2 quantum dot layer stacked together. The Cs2AgBiBr6 perovskite layer is in contact with the electron transport layer, and the CuAlS2 quantum dot layer is located on the side of the Cs2AgBiBr6 perovskite layer away from the electron transport layer.
5. The method for fabricating the photoelectric synaptic device as described in claim 4, characterized in that, The step of forming a composite light-absorbing layer on the side of the electron transport layer away from the substrate includes: Provide Cs2AgBiBr6 precursor solution and CuAlS2 quantum dot dispersion; The substrate, the electron transport layer, and the Cs2AgBiBr6 precursor solution are preheated. The Cs2AgBiBr6 precursor solution forms a Cs2AgBiBr6 precursor layer on the surface of the electron transport layer away from the substrate. The CuAlS2 quantum dot dispersion forms a CuAlS2 quantum dot dispersion layer on the surface of the Cs2AgBiBr6 precursor layer away from the electron transport layer. The composite light-absorbing layer is obtained by heat-treating the Cs2AgBiBr6 precursor layer and the CuAlS2 quantum dot dispersion layer. The temperature of the preheating treatment is 70℃~85℃, and the time of the preheating treatment is 5min~10min; The temperature of the heat treatment is 280℃~320℃, and the time of the heat treatment is 5min~10min.
6. The method for fabricating the photoelectric synaptic device as described in claim 5, characterized in that, The preparation steps of the Cs2AgBiBr6 precursor solution include: CsBr, BiBr3 and AgBr are mixed in a molar ratio of 2:(1.0~1.2):(1.0~1.2) in a first solvent and dispersed to obtain the Cs2AgBiBr6 precursor solution. Wherein, the first solvent is dimethyl sulfoxide, the dispersion treatment temperature is 55℃~75℃, and the dispersion treatment time is greater than or equal to 12 hours.
7. The method for fabricating the photoelectric synaptic device as described in claim 5, characterized in that, The preparation steps of the CuAlS2 quantum dot dispersion include: CuCl and Al(acac)3 are mixed in a molar ratio of 1:(0.8~1.2) in a second solvent, and after degassing, a first mixture is obtained. The first mixture is kept at 100℃~160℃ for 30 minutes or more to obtain the first reaction solution; The first reaction solution is kept at 145℃~160℃ for 15 minutes or more to obtain the second reaction solution; The second reaction solution is mixed with n-dodecyl mercaptan to obtain the third reaction solution; The third reaction solution is mixed with the sulfur precursor solution at 160℃~170℃ for 4 minutes and then kept at this temperature for 5 minutes to obtain the fourth reaction solution. The fourth reaction solution is reacted sequentially with the zinc shell precursor solution and the selenium shell precursor solution at 160℃~170℃ to obtain the fifth reaction solution. The fifth reaction solution was kept at 220℃~240℃ for more than or equal to 50 min to obtain CuAlS2 quantum dot stock solution. The CuAlS2 quantum dot stock solution was purified to obtain the CuAlS2 quantum dot dispersion.
8. The method for fabricating the photoelectric synaptic device as described in claim 7, characterized in that, The second solvent is a mixed solvent of 1-octadecene and oleic acid, wherein the volume ratio of 1-octadecene to oleic acid in the second solvent is 1:(0.8~1.2). The sulfur precursor solution is obtained by dissolving thioacetamide in a third solvent, which is a mixed solvent of 1-octadecene and n-dodecyl mercaptan, with a volume ratio of 1-octadecene to n-dodecyl mercaptan of (6~12):(1.5~4), and the concentration of thioacetamide is 0.00469 g / mL~0.00939 g / mL. The zinc shell precursor solution was obtained by dissolving Zn(St)2 in 1-octadecene, and the concentration of the zinc shell precursor was 0.125 g / mL to 0.188 g / mL. The selenium shell precursor solution was obtained by dissolving Se powder in 1-octadecene, and the concentration of the selenium shell precursor was 0.0131 g / mL to 0.0196 g / mL.
9. The method for fabricating the photoelectric synaptic device as described in claim 7, characterized in that, The step of purifying the CuAlS2 quantum dot stock solution to obtain the CuAlS2 quantum dot dispersion includes: The CuAlS2 quantum dot stock solution was mixed with the fourth solvent and then subjected to a first centrifugation process to obtain the supernatant. The supernatant was mixed with the fifth solvent and then subjected to a second centrifugation process to obtain CuAlS2 quantum dots. After drying, the CuAlS2 quantum dots are mixed with a sixth solvent to obtain the CuAlS2 quantum dot dispersion. Wherein, the fourth solvent is selected from toluene, the fifth solvent is selected from anhydrous ethanol, and the sixth solvent is selected from toluene; The first centrifugation process is carried out at a speed of 3000 rpm to 5000 rpm for a duration of 3 min to 5 min. The second centrifugation process is carried out at a speed of 12,000 rpm to 16,000 rpm for 5 min to 10 min.
10. The method for fabricating the photoelectric synaptic device as described in claim 4, characterized in that, The step of forming a top electrode layer on the side of the composite light-absorbing layer away from the electron transport layer includes: The top electrode layer is formed on the surface of the composite light absorption layer away from the electron transport layer using a photomask.